Periodontal disease and its impact on general health in Latin America. Section I: Introduction part I - Jorge Gamonal; Joel Bravo; Zilson Malheiros; Bernal Stewart; Alicia Morales; Franco Cavalla; Mariel Gomez (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: A high level of general and oral health are invaluable assets, a factor not always considered a basic human right for their better life quality. The mouth is a critical point of contact with the external environment, which is established when we talk, chew, swallow and when food digestion begins. From a perspective of the human condition, the mouth is crucial for the integration of sound, social appearance of the individual, and is one of the fundamental components of overall health. Therefore, not having an adequate level of oral health affects self-esteem, quality of life and people's general well-being.